Improved Enantioselectivity of Subtilisin Carlsberg towards Secondary Alcohols by Protein Engineering. (18th December 2017) - Dorau, Robin; Görbe, Tamás; Svedendahl Humble, Maria
Abstract: Generally, the catalytic activity of subtilisin Carlsberg (SC) for transacylation reactions with secondary alcohols in organic solvent is low. Enzyme immobilization and protein engineering was performed to improve the enantioselectivity of SC towards secondary alcohols. Possible amino‐acid residues for mutagenesis were found by combining available literature data with molecular modeling. SC variants were created by site‐directed mutagenesis and were evaluated for a model transacylation reaction containing 1‐phenylethanol in THF. Variants showing high E values (>100) were found. However, the conversions were still low. A second mutation was made, and both the E values and conversions were increased. Relative to that shown by the wild type, the most successful variant, G165L/M221F, showed increased conversion (up to 36 %), enantioselectivity ( E values up to 400), substrate scope, and stability in THF. Abstract : An acyl in the hole : The performance of the serine protease subtilisin Carlsberg (SC) is improved towards transacylation reactions by using secondary alcohols in THF. By enzyme immobilization, the enantioselectivity of SC is increased tenfold. By further protein engineering, an enzyme variant (G165L/M221F) shows increased conversion, enantioselectivity ( E >100), substrate scope, and stability in THF.